Perioperative Outcome of Dyssomnia Patients on Chronic Methylphenidate Use. (29th January 2014) - Stoicea, Nicoleta; Ellis, Thomas; Moran, Kenneth; Ackermann, Wiebke; Wilson, Thomas; Quevedo, Eduardo; Bergese, Sergio
Methylphenidate is frequently prescribed for attention deficit hyperactivity disorder, narcolepsy, and other sleep disorders requiring psychostimulants. Our report is based on 2 different clinical experiences of patients with chronic methylphenidate use, undergoing general anesthesia. These cases contrast different strategies of taking versus withholding the drug treatment on the day of surgery. From the standpoint of anesthetic management and patient safety, the concerns for perioperative methylphenidate use are mainly related to cardiovascular stability and possible counteraction of sedatives and anesthetics.